Techno-Environmental Analysis of Facade Integrated Photovoltaics and Electric Vehicle Charging for University Building - Khan, Sanjay; Sudhakar, K.; Mohd Hazwan, Yusof (Hindawi Publishing Corporation, 2022)
Electric vehicles (EV) are a relatively contemporary and emerging technology in the transportation and power sectors, with several economic and environmental advantages. However, there are still challenges associated with EV charging depending on on-grid electricity. University buildings that consume a lot of energy continue to rely on the grid and/or conventional fuel for consumption. In addition, EV Charging will create more challenges in meeting the demand; therefore, utilizing university rooftops for EV charging has high prospects of meeting the additional energy demand. In Malaysia, no such research has been presented that has explored the possibility of using academic institute rooftops for BIPV installation for EV Charging in terms of energy and environmental standpoint. The current study analyzes and evaluates a rooftop grid-connected Building Integrated photovoltaic (BIPV) system for generating electricity and EV charging at the University Malaysia Pahang, Malaysia, for EV charging. The system’s energy output has been simulated using the PVSyst in two scenarios, i.e., fully integrated with no ventilation and free mounted with air circulation. It was found that 7000 m2 of the selected building’s rooftop area could be used for panel installation. The panels’ total capacity was 1.069 MW, with total annual electricity production of 1587 MWh and 1669 MWh in respective scenarios. The proposed BIPV plant would reduce GHG emissions of 60,031 tons of CO2e in scenarios 1 and 61,191 tons of CO2 in scenario 2 compared to the emission produced by coal plants for the same amount of annual energy generation.